Design of Uniform Hollow Carbon Nanoarchitectures: Different Capacitive Deionization between the Hollow Shell Thickness and Cavity Size. Issue 9 (19th January 2023) - Tang, Yijian; Ding, Jiani; Zhou, Wenxuan; Cao, Shuai; Yang, Feiyu; Sun, Yangyang; Zhang, Songtao; Xue, Huaiguo; Pang, Huan
Abstract: Carbon‐based materials with high capacitance ability and fast electrosorption rate are ideal electrode materials in capacitive deionization (CDI). However, traditional carbon materials have structural limitations in electrochemical and desalination performance due to the low capacitance and poor transmission channel of the prepared electrodes. Therefore, reasonable design of electrode material structure is of great importance for achieving excellent CDI properties. Here, uniform hollow carbon materials with different morphologies (hollow carbon nanospheres, hollow carbon nanorods, hollow carbon nano‐pseudoboxes, hollow carbon nano‐ellipsoids, hollow carbon nano‐capsules, and hollow carbon nano‐peanuts) are reasonably designed through multi‐step template method and calcination of polymer precursors. Hollow carbon nanospheres and hollow carbon nano‐pseudoboxes exhibit better capacitance and higher salt adsorption capacity (SAC) due to their stable carbonaceous structure during calcination. Moreover, the effects of the thickness of the shell and the size of the cavity on the CDI performance are also studied. HCNSs‐0.8 with thicker shell (≈20 nm) and larger cavity (≈320 nm) shows the best SAC value of 23.01 mg g −1 due to its large specific surface area (1083.20 m 2 g −1 ) and rich pore size distribution. These uniform hollow carbon nanoarchitectures with functional properties have potential applications in electrochemistry related fields. Abstract : Homogeneous hollow carbon materials with different morphologies (HCNSs, HCNRs, HCNBs, HCNEs, HCNCs, HCNPs) are reasonably designed, and their capacitive deionization properties are explored. In addition, the influence of shell thickness and cavity size on CDI performance is explored.